Cardiovascular Implantable Electronic Device Infection and New Insights About Correlation Between Pro-inflammatory Markers and Heart Failure: A Systematic Literature Review and Meta-Analysis - Zerbo, Stefania; Perrone, Giulio; Bilotta, Clio; Adelfio, Valeria; Malta, Ginevra; Di Pasquale, Pietro; Maresi, Emiliano; Argo, Antonina (Frontiers in Cardiovascular Medicine, 2021)
Introduction: Surgical approaches to treat patients with abnormal pro-inflammatory parameters remain controversial, and the debate on the correlation between hematological parameter alteration in cardiac implantable electronic device (CIED) infection and the increase in mortality continues. Methods: We performed a systematic review using the PubMed, Scopus and Cochrane Library databases. Twenty-two articles from May 2007 to April 2020 were selected and divided into according to following topics: prevalence of microbes in patients with CIED infection; characteristics of patients with CIED infection; comparison between patients who underwent and did not undergo replantation after device extraction; and correlation between alteration of hematological parameters and poor prognosis analysis. Results: Epidemiological analysis confirmed high prevalence of male sex, staphylococcal infection, and coagulase-negative staphylococci (CoNs). The most common comorbidity was heart failure. Complete removal of CIED and antimicrobial therapy combination are the gold standard. CIED replacement was associated with higher survival. High pre-operative white blood cell count and C-reactive protein levels increased the risk of right ventricular failure (RVF) development. Increased red blood cell distribution width (RDW) value or decreased platelet count was correlated with poor prognosis. No correlation was noted between pre-operative leukocytosis and CIED infection. Discussion: A relevant correlation between leukocytosis and RVF was observed. Heart failure may be related to high RDW values and decreased platelet count. Data on the correlation between hematological parameter alteration and poor prognosis are missing in many studies because of delayed implantation in patients showing signs of infection.